2007
DOI: 10.1017/s0022215107008791
|View full text |Cite
|
Sign up to set email alerts
|

Mutational falsetto: intervention outcomes in 45 patients

Abstract: In the light of objective evaluations, and by applying the study treatment protocol, these results suggest that normal voice can be maintained after intervention, at six months' follow up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
17
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 15 publications
(33 reference statements)
9
17
0
4
Order By: Relevance
“…Results show that all patients had a decrease in the mean, maximum, and minimum fundamental frequency values, characterizing lower emissions. This result is correlated to the auditory-perceptual analysis in this study, with presence of lower pitch, which agrees with literature results (7)(8)(9)(10) . A study with ten teenagers with mutational falsetto in preand post-therapy conditions showed mean f0 values of 221 Hz and 119 Hz, respectively.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Results show that all patients had a decrease in the mean, maximum, and minimum fundamental frequency values, characterizing lower emissions. This result is correlated to the auditory-perceptual analysis in this study, with presence of lower pitch, which agrees with literature results (7)(8)(9)(10) . A study with ten teenagers with mutational falsetto in preand post-therapy conditions showed mean f0 values of 221 Hz and 119 Hz, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…These findings agree with literature that indicates speech-language therapy as the elected approach to treat mutational dysphonia, showing good results in the improvement of patients' voices (3,(7)(8)(9)(10) . With regards to auditory-perceptual analysis, the overall grade of dysphonia (G) improved in all the participants after intervention, corroborating other studies (7)(8)(9) . The pitch parameter was different in pre-and post-therapy conditions, in all analyzed voices, and it was a distinguishing factor.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is in corrobo ration with the study previously carried by Dagli M et al, 5 Alam N et al 6 A study done by Hammarberg B et al 7 which consisted of 10 patients of mutational falsetto, in pre and post therapy condition showed mean F0 values of 221 Hz and 119 Hz respectively, which is similar to our study. Another study done by Cassol M et al 8 consisting…”
Section: Discussionsupporting
confidence: 93%
“…5,7,8 In this study, voice therapy also helped to enhance confi dence and self image of the speaker due to psycho social improvement which is confirmed by decrease in emotional component of VHI score. These findings are similar to a study done by Alam N et al 6 Further studies consisting of larger group of patients are needed with newer techniques of acoustic analysis and quality of life measures to confirm the results and to improve our understanding about mutational falsetto.…”
Section: Discussionsupporting
confidence: 56%